Um olhar da periferia: Dom Fernando Gomes dos Santos e o impacto do Concílio Vaticano II no catolicismo goiano - Gonçalves Neto, Orlandino (2019)
The aim of this dissertation is to perceive the impact of the Vatican II Council in the Brazilian Catholicism based on the vison of the periphery (Mid-West of Brazil). The chronological scope extends from the convocation of the the Vatican II Council (1959) to the realization of the General Conference of the Latin American Episcopate in Medellin, Colombia (1968). Our theoretical methodological proposal revolves around the representation and appropriation concepts according to Chartier (1988), Pesavento (1994) and Dussel (1986). In our study we will discuss with the bishops and the church agents who took part in the elaboration of the new postulate of catholic doctrines and practices as they reproduced the message coming from Rome highlighting as well the means which was used by them to implement the changes. The Vatican II Council was not only an ecclesiastical phenomenon but also responded to the internal (Church) and external (Society) expectations, according to Beozzo (2003). It can also be appointed as an institutional, theological and parcatical because it implies a return to the origins of the primitive Christianism. Finally we will try to understand the option of the Church for the poor.